2020
DOI: 10.1101/2020.06.03.132365
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of the radiated brain microenvironment on a panel of human patient-derived xenografts

Abstract: ObjectiveRadiotherapy, combined with surgical resection and chemotherapy, remains a first-line treatment for infiltrative gliomas. However, these tumor are not surgically curable, and often recur, even within the prior radiation field, and may demonstrate a more aggressive phenotype. We recently demonstrated that the radiated brain tumor microenvironment promotes tumor aggressiveness in an orthotopic patient-derived xenograft (PDX) model of glioblastoma (Mayo GBM 143). Importantly, high grade gliomas display d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…This simple view has recently shifted towards recognizing the central importance of the TME 15 and a growing body of literature are now investigating the impacts of RT on TME and tumor resistance. At least, three recent publications reported that an irradiated TME increases GBM aggressiveness in orthotopic murine models 6,16,17 with no or limited investigation of underlying mechanisms. In the present work, using relevant in vitro and in vivo models, we demonstrate that alteration of the vascular TME by RT directly impacts relapsing tumor aggressiveness upon radiation.…”
Section: Discussionmentioning
confidence: 99%
“…This simple view has recently shifted towards recognizing the central importance of the TME 15 and a growing body of literature are now investigating the impacts of RT on TME and tumor resistance. At least, three recent publications reported that an irradiated TME increases GBM aggressiveness in orthotopic murine models 6,16,17 with no or limited investigation of underlying mechanisms. In the present work, using relevant in vitro and in vivo models, we demonstrate that alteration of the vascular TME by RT directly impacts relapsing tumor aggressiveness upon radiation.…”
Section: Discussionmentioning
confidence: 99%